Evaluation of role of computed tomography scan brain in children with generalized seizures - Chaudhary, G S; Chaudhary, V (Indian Journal of Child Health, 2016)
Objective: To evaluate the role of computed tomography (CT) scan brain in children over the age of 1 year with generalized seizures. Design: Prospective, hospital-based study. Materials and Methods: Children of 1-12 years presenting with generalized seizures in pediatric outpatient department and emergencies were subjected for CT scan brain with contrast along with other appropriate investigations after stabilization. Results: A total of 101 cases of children with generalized seizures underwent CT scan brain, 36 cases (35.64%) were found to have CT brain abnormalities. Conclusion: CT brain should be considered in children with generalized seizures in health care settings where magnetic resonance imaging is either unavailable or unaffordable.